2022
DOI: 10.1007/s40122-022-00409-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and Risk Factors for Prescription Opioid Misuse, Abuse, Diversion and Doctor Shopping in Japan: A Survey Study

Abstract: Introduction Opioid use disorder is a global problem. Although opioid analgesics are prescribed less frequently in Japan than in many other countries, the rate of aberrant prescription opioid-taking behaviors in Japan is unknown. Methods An internet survey was conducted to estimate the prevalence of and risk factors for prescription opioid misuse, abuse, diversion and doctor shopping in Japanese subjects with chronic pain who had been prescribed opioid analgesics. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…In the UK, opioid misuse and related deaths are growing, with Scotland reporting the highest opioid-related mortality and one-year use increase in Europe (Alenezi et al , 2021). A recent survey in Japan reported that 45.5% of participants misused opioids (Takasusuki et al , 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In the UK, opioid misuse and related deaths are growing, with Scotland reporting the highest opioid-related mortality and one-year use increase in Europe (Alenezi et al , 2021). A recent survey in Japan reported that 45.5% of participants misused opioids (Takasusuki et al , 2022).…”
Section: Introductionmentioning
confidence: 99%